2021
DOI: 10.5535/arm.20129
|View full text |Cite|
|
Sign up to set email alerts
|

The Clinical Features of Preschool Children With Speech and Language Disorder and the Role of Maternal Language

Abstract: Objective To retrospectively review the characteristics of preschool children with speech and language disorders to determine their clinical features and compares the average degrees of language delay based on hospital visit purposes, language developmental delay causes, and maternal language. Methods One thousand one hundred two children (832 males, 270 females) with the chief complaint of language or speech problems who underwent language assessment for the first time were included. Their medical records, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Delayed speech and language complaints are a common problem among preschool children (9). It has been reported that 6-7% of children have delays in speech and language development when they reach the school starting age (10).…”
Section: Discussionmentioning
confidence: 99%
“…Delayed speech and language complaints are a common problem among preschool children (9). It has been reported that 6-7% of children have delays in speech and language development when they reach the school starting age (10).…”
Section: Discussionmentioning
confidence: 99%
“…Speech and language delay constitutes a frequent disorder in early childhood development affecting approximately 2% to 11% of preschool children and around 9% to 17% of children aged about 2 years (Choi et al, 2011;Kim et al, 2001;Kim et al, 2021). Early intervention is critical for children with language delay in order to avoid academic and social difficulties later in life.…”
Section: Introductionmentioning
confidence: 99%